The Effect of Fermented Corn Cobs by Adding Different Sources of Carbohydrates on The Content of Dry Matter, Organic Matter, and Crude Protein as Ruminant Feeding - Sukra, Pio; Mega Sari, Rica; Astuti, Tri (Department of Agriculture, 2023)
This study aims to determine the effect of the fermentation of corn cobs using the Panarochaeta Chrisosporium white coating fungus with the addition of a different source of carbohydrates to the content of dry matter, organic matter, and crude protein. This study used a completely random design. Consists of 4 treatments and four replications in each treatment. The need in this study was a dose of carbohydrate source different from the use of inoculum of white fungus (Panarochaeta chrisosporium) 7%. P0 = corn cob + without carbohydrate, P1 = corn cob + 10%rice bran, P2 = corn cob + tapioca flour 10%, P3 = corn cob + 10%molasses. The parameters measured in this study are the content of dry matter, organic matter, and crude protein. The results showed no different effects (P> 0.05) on the content of dry matter, and the effects were highly significant (p <0.01) on the content of organic material and crude protein content. From the results of the study, it can be concluded that the effect of fermented corn cob is the best on the content of organic material and crude protein with the addition of carbohydrate sources using tapioca flour.